Methods for the control of bacterial plaque during the post-orthodontic fixed containment phase. narrative review - Colán Jarrín, Anggie Melissa (2019)
After orthodontic treatment is completed, the main objective is to maintain long-term occlusal stability by preventing recurrence, and this is possible using fixed post-orthodontic retention. The purpose of this research was to evaluate the different methods that exist for the control of bacterial plaque in patients with fixed post-orthodontic containment and how they could affect the state of periodontal health. There are many short-term and long-term studies on this subject, but not one that actually indicates that there are any negative effects. However, it is known that these patients have a tendency to accumulate a greater amount of bacterial plaque, which leads to a higher risk of calculus formation, gingival inflammation, gingival recession, and lingual and interproximal caries, and periodontal disease. For this reason, most studies highlight good oral hygiene as a determining factor to guarantee periodontal health and attend follow-up appointments with the orthodontist to evaluate the physical state of the appliance, in order to avoid possible fractures or failures in the dental system. adhesion of the fixed restraint and give immediate treatment if this has already occurred. The literature does not indicate a specific oral technique for patients with post-orthodontic fixed retention, but it does indicate that good periodontal health can be achieved if the patient maintains adequate oral hygiene and that the orthodontist plays an important role in motivating the patient to achieve it.